Variabel-variabel yang Mempengaruhi Rendahnnya Partisipasi Politik Masyarakat dalam Pilkada Walikota dan Wakil Walikota Padang Tahun 2008 - Hendrik, Doni (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2010)
As a capital city of West Sumatra Province,Â Padang has run its first district election for major in 2008. Based on statistical count, the vote of â€œPilkadaâ€ Padang in the election is just 51%. That is new record in Indonesian political history, because citizen political participation always more than 75% in the past. Because of that, the main question revealed in this study is what variabels has influenced the lack of participation in Padang â€œPilkadaâ€ in 2008? To find the answer, a study has been conducted. This study use the quantitative and descriptive method. Political participation theory has been used to explain the problems. This study found that the lack of socialization of Pilkada by KPU and the lack of Political Consciousness of Padang citizen has become variables that influence the turn out of the vote in Padang Pilkada in 2008. Kata Kunci: Partisipasi politik, penurunan suara, kesadaran politik, sosialisasi politik